Responses to Racism within Black Families in Cartagena de Indias - Villarreal, Kristell Andrea; Marrugo Monterrosa, Heiver; Ríos Fernández, Javier; Ochoa Ramos, Ana Cecilia (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This article describes some of the responses to everyday racism that occurs within some black families from Cartagena. The categories of analysis of this work were established from the forms of everyday racism conceptualized by Philomena Essed (1991). The data used were obtained through twenty semi-structured interviews. We worked with people who recognize themselves as black, the practices they described took place within the family nucleus where they were formed, but also the family nucleus that they formed during their adulthood. It is concluded that in many black families from Cartagena are spaces where identity is managed and where the pillars are built, so that subjects can acquire tools that allow them to improve their capacity for social mobility, but it is also a space where racist ideologies can be (re)produced under a protectionist and paternalistic premise.